Research trends of facial nerve injury after cerebellopontine angle tumor: CiteSpace-based bibliometric analysis - Xinxin Li; Bing Bai; Beibei Nie (Frontiers in Neurology)
BackgroundA bibliometric analysis was conducted to understand the current research status and trends in facial nerve injury after cerebellopontine angle (CPA) tumors to identify new perspectives for future research.MethodsCiteSpace was used to visualize and analyze relevant literature included in the CNKI and WanFang databases, and the Web of Science Core Collection from 2015 to 2024. Chinese literature was deduplicated using NoteExpress.ResultsA total of 7,021 studies was retrieved, showing a pattern of rapid increase in this research area over the past 10 years. Protection and management of the facial nerve in surgery and early recognition of facial nerve injury were the research hotspots and trends.ConclusionThis study emphasizes the importance of intraoperative protection and management of the facial nerve. Limited research has addressed the postoperative facial nerve injury from the perspective of functional rehabilitation and patient psychology. These areas need more attention and focused research.